Association of women leaders in the C-suite with hospital performance. Issue 4 (14th December 2021) - Christopher, Adrienne N; Nembhard, Ingrid M; Wu, Liza; Yee, Stephanie; Sebastian, Albertina; Charan, Nidhi; Betchen, Simone
Abstract : Background: Women comprise 50% of the healthcare workforce, but only about 25% of senior leadership positions in the USA. No studies to our knowledge have investigated the performance of hospitals led by women versus those led by men to evaluate the potential explanation that the inequity reflects appropriate selection due to skill or performance differences. Methods: We conducted a descriptive analysis of the gender composition of hospital senior leadership (C-suite) teams and cross-sectional, regression-based analyses of the relationship between gender composition, hospital characteristics (eg, location, size, ownership), and financial, clinical, safety, patient experience and innovation performance metrics using 2018 data for US adult medical/surgical hospitals with >200 beds. C-suite positions examined included chief executive officer (CEO), chief financial officer (CFO) and chief operating officer (COO). Gender was obtained from hospital web pages and LinkedIn. Hospital characteristics and performance were obtained from American Hospital Directory, American Hospital Association Annual Hospital Survey, Healthcare Cost Report Information System and Hospital Consumer Assessment of Healthcare Providers and Systems surveys. Results: Of the 526 hospitals studied, 22% had a woman CEO, 26% a woman CFO and 36% a woman COO. While 55% had at least one woman in the C-suite, only 15.6% had more than one. Of the 1362 individuals who held one of the three C-suite positions, 378 were women (27%). Hospital performance on 27 of 28 measures (p>0.05) was similar between women and men-led hospitals. Hospitals with a woman CEO performed significantly better than men-led hospitals on one financial metric, days in accounts receivable (p=0.04). Conclusion: Hospitals with women in the C-suite have comparable performance to those without, yet inequity in the gender distribution of leaders remains. Barriers to women's advancement should be recognised and efforts made to rectify this inequity, rather than underusing an equally skilled pool of potential women leaders.